The Role of Higher Education Institutions in Preparing Youth to Manage a Sustainability-Oriented Future Workplace - Mona Betour El Zoghbi; Wim Lambrechts (The Central European Review of Economics and Management (CEREM), 2019)
Aim: This paper aims to highlight the different forms, levels and pathways of engagement with climate change and sustainability of young people living in different contexts of vulnerability and adaptability. It explores different perspectives and viewpoints of youth regarding complex and uncertain issues related to climate change and sustainability as well as their future role on the workplace.Research Methods: The critical interpretivist study was conducted in the Netherlands and South Africa, and participants were undergraduate and postgraduate university students from diverse socio-demographic and academic backgrounds in the two countries. The study applied various methods of data collection including focus groups, interviews, policy document reviews as well as participant-observation at several youth and environmental events and forums.Conclusions/Findings: Key findings highlight the importance of building resilience and empowering academic and civic platforms that enhance young people's competences to manage sustainability-oriented lifestyles and workplaces through critical, creative, and collaborative processes.
Keywords: 330; Youth education; Engagement; Empowerment; Climate change; Sustainability